Prevalence of Anemia among Patients with Diabetes Mellitus Attending a Tertiary care Center in Nepal: A Descriptive Cross-sectional Study - Adhikari, P; Acharya, A; Bhattarai, K Kritika; Gaire, S (Journal of Diabetes and Endocrinology Association of Nepal, 2024)
Background: Anemia is a common yet often underdiagnosed complication in individuals with diabetes mellitus (DM), associated with increased risk of microvascular and macrovascular complications. Despite the growing burden of diabetes in Nepal, limited data exist on the prevalence of anemia in this population. This study aimed to determine the prevalence of anemia among patients with DM and explore its association with glycemic control and other clinical parameters.Methods: A descriptive cross-sectional study was conducted from April to October 2024 at Nepal Medical College Teaching Hospital. A total of 373 diabetic patients were enrolled using convenient sampling. Hemoglobin levels were assessed to diagnose anemia based on WHO criteria (